Causal Relationship Between Endometriosis and Pelvic Inflammatory Diseases: Mendelian Randomization Study - Liu K; Liu X; Cao T; Cui X; Sun P; Zhang L; Wu X (Dove Medical Press, 2024)
Kang Liu, Xiaochun Liu, Tao Cao, Xianmei Cui, Pengyu Sun, Liang Zhang, Xiaoqin Wu Department of Obstetrics and Gynecology, Shanxi Bethune Hospital & Shanxi Academy of Medical Sciences, Shanxi Bethune Hospital Affiliated to Shanxi Medical University, Taiyuan, 030032, People's Republic of ChinaCorrespondence: Xiaoqin Wu, Department of Obstetrics and Gynecology, Shanxi Bethune Hospital & Shanxi Academy of Medical Sciences, Shanxi Bethune Hospital affiliated to Shanxi Medical University, Taiyuan, 030032, People's Republic of China, Email liukang1212@sxmu.edu.cnObjective: This study explores the causal relationship between endometriosis and pelvic inflammatory diseases (PID).Methods: The study utilized genome-wide association study (GWAS) datasets for endometriosis ("finn-b-N14_ENDOMETRIOSIS") and PID ("finn-b-N14_OTHFEMPELINF"). Subsequently, two-sample Mendelian randomization (MR) analyses were conducted using inverse variance weighting (IVW), Egger regression (MR-Egger), and weighted median (WM) methods. Heterogeneity was evaluated using Cochran's Q test, and in case of detected outliers, they were removed for re-evaluation of MR causality.Results: From the endometriosis GWAS dataset, 33 single nucleotide polymorphisms (SNPs) were selected as instrumental variables. All three methods, IVW (OR = 1.39, P < 1× 10− 8), MR-Egger (OR = 1.41, P = 0.003), and WM (OR = 1.37, P = 1.16× 10− 5) confirmed a causal relationship between endometriosis and PID. The association between endometriosis and pelvic inflammation remained unaffected by the exclusion of individual SNPs. Lastly, Cochran's Q test and funnel plots showed no evidence of SNP asymmetry.Conclusion: The results of the MR analysis support a potential causal relationship between endometriosis and an increased risk of PID.Keywords: endometriosis, pelvic inflammatory diseases, genome-wide association study, Mendelian randomization